Richard A. Rossmiller: A Prophet Even in His Own Land - An Interview - Terry G. Geske; Deborah A. Verstegen (Educational Considerations, 2004)
In May 2004, Richard A. Rossmiller received the Alumni Achievement Award from the School of Education at the University of Wisconsin-Madison honoring him for his many accomplishments.